Patients with inflammatory bowel disease are more hesitant about Coronavirus disease 2019 vaccination - Kwon, Hyuk Joon; Panagos, Katherine; Alizadeh, Madeline; Bell, Mack; Bourmaf, Mohammad; Zisman, Erin; Paul, Pinkle; Sibel, Lauren; Wong, Uni (Frontiers in Medicine, 2022)
Despite the impact of the Coronavirus Disease 2019 (COVID-19) pandemic, vaccine hesitancy remains common in the general public and patients with Inflammatory Bowel Diseases (IBD). We sought to examine the reasons for vaccine hesitancy in patients with IBD. In this case-control study, we performed a retrospective chart review of 1349 IBD patients and 215 non-IBD patients seen at University of Maryland Medical Center, a tertiary referral medical center, between March 2020 and October 2021. Data obtained included demographics, vaccination records, disease history, number of IBD-related surgeries, and IBD medications. 813/1349 (60.3%) IBD patients received at least one dose of either the Pfizer/BioNTech, Moderna, or Johnson & Johnson vaccines. In a multivariate logistic regression, COVID vaccination was found to be positively associated with older age (p-value=1.65e-5), female sex (p= 0.00194), Asian and White races (p= 0.02330, 0.00169), number of clinic visits (p=1.11e-08), and biologic use (p= 7.82e-5). There was no association between vaccination and other types of vaccination nor with the use of other IBD medications. There was a negative association between vaccination status and the total number of IBD related surgeries (p= 0.02857). In non-IBD patients, only the number of clinic visits was positively associated with COVID-19 vaccination. Although the majority of IBD patients are immunosuppressed, COVID-19 vaccination rate was only 60.3%. Younger adults, males, African Americans, and those requiring IBD-related surgeries were less likely to receive COVID-19 vaccine. Healthcare providers need to recognize these potential risk factors for COVID-19 vaccine hesitancy.